Circulating Follicular Helper and Follicular Regulatory T Cells Are Severely Compromised in Human CD40 Deficiency: A Case Report - Cicalese, Maria Pia; Gerosa, Jolanda; Baronio, Manuela; Montin, Davide; Licciardi, Francesco; Soresina, Annarosa; Dellepiane, Rosa Maria; Miano, Maurizio; Baselli, Lucia Augusta; Volpi, Stefano; Dufour, Carlo; Plebani, Alessandro; et al. (Frontiers in Immunology, 2018)
Mutations in genes that control class switch recombination and somatic hypermutation during the germinal center (GC) response can cause diverse immune dysfunctions. In particular, mutations in CD40LG, CD40, AICDA or UNG cause hyper-IgM syndrome (HIGM), a heterogeneous group of primary immunodeficiencies. Follicular helper (Tfh) and follicular regulatory (Tfr) T cells play a key role in the formation and regulation of GCs, but their role in HIGM pathogenesis is still limited. Here, we found that compared to CD40L- and AID-deficient patients, circulating Tfh and Tfr cells were severely compromised in terms of frequency and activation phenotype in a child with CD40 deficiency. These findings offer useful insight for human Tfh biology, with potential implications for the understanding of molecular basis of HIGM syndrome caused by mutations in CD40.